Influence of diffusive processes on the border metal-lubrication upon the development of not permissible kinds of weary - Назаренко, П. В.; Дмитриченко, Н. Ф.; Мнацаканов, Р. Г.; Братица, Л. С. (Proceedings of National Aviation University (archive), 1998)
Considered is method of the lubricant tribo-technical features on the basis of parameters registered under unstable operating conditions of tribo-technical systems with local contact. The following experimental results are obtained: the influence of unstable modes of operation and physic and mathematical features of thin blanket of the process of lubrication organization for different groups of lubricants. The developed method of preliminary estimation of lubricant tribo-technical features is based on obtained results mentioned above